2016
DOI: 10.1007/s00167-016-4113-2
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow lesions and subchondral bone pathology of the knee

Abstract: Bone marrow lesions (BMLs) around the knee are a common magnetic resonance imaging (MRI) finding. However, despite the growing interest on BMLs in multiple pathological conditions, they remain controversial not only for the still unknown role in the etiopathological processes, but also in terms of clinical impact and treatment. The differential diagnosis includes a wide range of conditions: traumatic contusion and fractures, cyst formation and erosions, hematopoietic and infiltrated marrow, developmental chond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
99
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 89 publications
1
99
0
13
Order By: Relevance
“…However, this analysis failed to prove significant correlations amongst the diagnostic techniques applied. This result is in line with the current literature reporting on difficulties to establish a correlation between diagnosed BML, pain, and MRI findings [7,9]. An explanation for these difficulties may be differences in the dynamics when the diagnostic techniques are applied.…”
Section: Correlationssupporting
confidence: 91%
“…However, this analysis failed to prove significant correlations amongst the diagnostic techniques applied. This result is in line with the current literature reporting on difficulties to establish a correlation between diagnosed BML, pain, and MRI findings [7,9]. An explanation for these difficulties may be differences in the dynamics when the diagnostic techniques are applied.…”
Section: Correlationssupporting
confidence: 91%
“…9 The cellular processes associated with BMLs have implications for the mechanical integrity of the tissue. [11][12][13] Bone turnover, local inflammation, and consequent bone attrition all translate into loss of mechanical integrity, subchondral bone collapse, rapidly progressive cartilage loss, and joint deterioration. 6,9,11,14,15 Clinically, BMLs have been correlated to signs of joints surface deformation and increased symptoms of knee pain.…”
mentioning
confidence: 99%
“…Early injuries with no evidence of cartilage injury may, on occasion, be reversible similar to early subchondral bone injury in the horse. 23 A study in humans with bone marrow lesions in the knee 24 who underwent SCP for the MRI lesions associated with osteoarthritis found that 88% of patients reported improvement in pain following the procedure and 92% of patients did not need to move on to a total knee arthroplasty at the 2-year follow-up. 24 Another study in 2016 14 evaluating patients that underwent SCP in conjunction with arthroscopy found a significant improvement in pain and function scores in these patients, with 70% of these patients no longer requiring a total knee arthroplasty at the 2-year follow-up.…”
Section: Discussionmentioning
confidence: 99%